Cross-border copyright protection in the UK and China: from copyright law and private international law perspectives - Yang, Tianwa (2021)
Traditionally, copyright protection is territorial. As international exchange and Internet technology develop, the nation-by-nation exploitation of copyright is being replaced by cross-border exploitation; thus, foreign-related copyright disputes arise more frequently than before. Accordingly, there is an increasing relevance of applying private international law (or conflict of laws) in the efficient settlement of copyright disputes and the effective enforcement of copyright law. This research focuses on the comparative study concerning cross-border protection of copyrighted work in the UK and China from two perspectives: copyright law and private international law. It first compares differences concerning the substantive issues to examine whether those differences will pose problems for China in protecting foreign copyright. The examination of copyright law will also contour the general picture of substantive issues which have implication for the subsequent discussion on jurisdiction and choice of law. This thesis will primarily explore the international jurisdictional rule and the choice-of-law rule concerning copyright infringement in both countries. It examines jurisdictional factors related to defendants and factors related to the dispute in law, and the application of approaches in practice to assess whether the traditional approaches require refinement in copyright infringement. Since lex loci protectionis has been widely accepted in law and thoroughly examined by the doctrinal study, this thesis will focus on the application of lex loci protectionis in practice to highlight the misunderstanding of this concept, the errors in application and the potential problem of numerous overlapping national copyright laws. This thesis will evaluate different approaches to fine-tune jurisdiction and choice of law concerning copyright infringement.